Tissue Factor-Targeted “O2-Evolving” Nanoparticles for Photodynamic Therapy in Malignant Lymphoma - Li, Ziying; Yin, Yanxue; Jin, Weiwei; Zhang, Bo; Yan, Han; Mei, Heng; Wang, Huafang; Guo, Tao; Shi, Wei; Hu, Yu (Frontiers in Oncology, 2020)
Vascular-targeted PDT (vPDT) has produced promising results in the treatment of many cancers, including drug-resistant ones, but little is known about its efficacy in lymphoma. Unfortunately, the lack of a specific therapeutic target and a hypoxic microenvironment for lymphoma jeopardizes the efficacy of vPDT severely. In this study, we designed a lymphoma tissue factor-targeted “O2-evolving” strategy combining PDT with catalase and HMME-encapsulated, EGFP-EGF1-modified PEG-PLGA nanoparticles (CENPs) to boost PDT efficiency; this combination takes advantage of the low oxygen tension of lymphoma. In our results, CENPs accumulated effectively in the vascular lymphoma in vivo and in vitro, and this accumulation increased further with PDT treatment. Per positron emission tomography imaging, combining CENPs with PDT inhibited lymphoma glucose metabolism significantly. The expression of hypoxia-inducible factor (HIF)-1α in the entrapped catalase groups reduced markedly. These data show that the combined administration of PDT and CENPs can prompt tissue factor-cascade-targeted and self-supply of oxygen and that it has a good therapeutic effect on malignant lymphoma.